2004
DOI: 10.1097/01.alc.0000131298.32045.96
|View full text |Cite
|
Sign up to set email alerts
|

Nursing From an Ethanol‐Intoxicated Dam Induces Short‐ and Long‐Term Disruptions in Motor Performance and Enhances Later Self‐Administration of the Drug

Abstract: Early experiences with alcohol comprising interactions with an alcohol-intoxicated dam result in motor impairment and enhanced ethanol intake later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 75 publications
1
46
0
Order By: Relevance
“…In rats, EtOH oral consumption markedly decreases as concentration of the drug reaches approximately 6% (Kiefer et al, 1987;Ponce et al, 2004). Kiefer et al (2005) observed substantial aversive orofacial reactions in adult rats intraorally stimulated with ethanol (10 % v/v).…”
Section: Discussionmentioning
confidence: 95%
“…In rats, EtOH oral consumption markedly decreases as concentration of the drug reaches approximately 6% (Kiefer et al, 1987;Ponce et al, 2004). Kiefer et al (2005) observed substantial aversive orofacial reactions in adult rats intraorally stimulated with ethanol (10 % v/v).…”
Section: Discussionmentioning
confidence: 95%
“…Another aim was to conduct all intake tests during the adolescent stage of development. Phases 1 and 4 of the protocol were designed on the basis of previous two-bottle choice studies conducted in our laboratory (Pepino et al, 2004; Ponce et al, 2004, 2008) which had proven useful to detect early ethanol exposure effects.…”
Section: General Methodsmentioning
confidence: 99%
“…For each animal, ethanol-intake score was calculated in terms of grams of absolute ethanol consumed per kilogram of body weight. Molina and Spear (e.g., Pepino, Abate, Spear, & Molina, 2004;Ponce, Pautassi, Spear, & Molina, 2004), voluntary ethanol-drinking sessions were conducted in standard microisolator cages equipped with two graduated drinking tubes (volume: 30 ml with 0.1 ml graduation) mounted on one wall of the cage. Each voluntary intake session was preceded by 22 hr of water deprivation, and each intake session lasted for 2 hr.…”
Section: Ethanol Intakementioning
confidence: 99%